Characteristics and long‐term survival of patients with left ventricular non‐compaction cardiomyopathy. (16th September 2022) - Demir, Emre; Bayraktaroğlu, Selen; Çinkooğlu, Akın; Candemir, Aytaç; Candemir, Yeşim B.; Öztürk, Rıza O.; Dadaş, Ömer F.; Orman, Mehmet N.; Zoghi, Mehdi; Akıllı, Azem; Ceylan, Naim; Gürgün, Cemil; et al.
Abstract: Aims: Left ventricular non‐compaction cardiomyopathy (LVNC) is a poorly understood entity resulting in heart failure. Whether it is a distinct form of cardiomyopathy or an anatomical phenotype is a subject of discussion. The current diagnosis is based on morphologic findings by comparing the compacted to non‐compacted myocardium. The study aimed to compare demographic and prognostic variables of patients with dilated cardiomyopathy (DCM) and LVNC. Emphasis was given to cardiac magnetic resonance (CMR) imaging analysis. Data on survival were also assessed. Methods and results: We retrospectively evaluated the characteristics and outcomes of 262 non‐ischaemic cardiomyopathy patients with LVNC and DCM phenotypes. Petersen's CMR criteria of non‐compacted to the compacted myocardial ratio 2.3 were used to diagnose LVNC. The primary endpoint was a composite endpoint of major adverse cardiovascular events comprising cardiovascular‐related death, left ventricular assisted device implantation, or heart transplantation. A total of 262 patients with CMR data were included in the study. One hundred fifty‐five patients who fulfilled CMR criteria were diagnosed as LVNC. CMR findings revealed that LVNC patients had higher left ventricular end‐diastolic (137.2 ± 51.6, 116.8 ± 44.6, P  = 0.002) and systolic volume index (98.4 ± 49.5, 85.9 ± 42.7, P  = 0.049). Cardiac haemodynamics, cardiac output (5.61 ± 2.03, 4.96 ± 1.83; P  = 0.010), stroke volume (73.9 ± 28.8, 65.1 ± 25.1; P  = 0.013), and cardiac index (2.85 ± 1.0, 2.37 ± 0.72; P  < 0.0001), were higher in LVNC patients. Of all the 249 patients, 102 (40.9%) patients demonstrated late gadolinium enhancement (LGE). According to Petersen's criteria, the Kaplan–Meier survival outcome did not reveal significant differences (hazard ratio [HR]: 1.53, 95% confidence interval [CI]: [0.89–2.63], P  = 0.11). The presence or pattern of LGE did not show significant importance for endpoint‐free survival. Most of the sub‐epicardial LGE pattern was found in LVNC patients (94.4%). When receiver operator characteristics analysis was applied to NC/C ratio to discriminate the primary endpoint, a higher NC/C ratio of 2.57 was associated with adverse events (HR: 1.90, 95% CI: [1.12–3.24], P  = 0.016). Conclusions: Our study questions the criteria being used for the diagnosis of LVNC. Further evaluation of CMR variables and association of these findings with demographic variables and survival is mandatory.